Prevalence of Asymptomatic Gallstone during Routine Ultrasonography and its Associated Factors: Cross-Sectional Study from a Tertiary Care Teaching Hospital (GAIMS Journal of Medical Sciences, 2024)
Background: Gallstones are the most important risk factor for gall bladder carcinoma. Understanding the burden of asymptomatic gallstone and its associated factors is essential to identify risk group likely to develop complication.Objectives: To estimate the burden of asymptomatic gallstone (AGS) and assess the factors contributing towards the same.Material and methods: A cross-sectional study was done during February to August 2023 in a tertiary care teaching hospital among adults aged above 18 years undergoing ultrasound of the abdomen as a part of routine master health check-up. A questionnaire was used collect the socio-demographic details, medical history and laboratory investigation. A total 1300 individuals were screened for AGS and included for analysis.Results: The mean age of study participants was 55.99 ± 15.83 years. The study found 36 individuals with AGS i.e 2.8% (95% CI:1.9-3.8%). The mean size of gallstone was 8.19 ± 4.6 mm with a range of 2 to 25 mm. Medical condition such as diabetes, hypertension and body mass index was found to be associated with AGS (p